Manajemen Program Jumat Religi dalam Peningkatan Mutu Pembelajaran Agama Islam di UPT SMP Negeri 5 Medan - Nanda Arifa Albi; Hasrian Rudi Setiawan (Integrasi: Jurnal Studi Islam dan Humaniora, 2023)
This study aims to describe the implementation of religious Friday program management which includes planning, organizing, implementing, and monitoring and evaluating in improving the quality of Islamic religious learning at UPT SMP Negeri 5 Medan. This study uses a qualitative research method with a phenomenological approach. Data collection techniques used are: observation, interviews, and documentation studies. Data analysis was carried out using techniques: selecting, presenting data, and drawing conclusions. The research results obtained: 1) Religious Friday activity planning in improving the quality of Islamic religious learning has been carried out well. The first step in planning this religious Friday activity is to make a set of activities; 2) Organizing religious Friday program activities is carried out by maximizing all the potential that exists in schools, both human resources and existing facilities and infrastructure resources to achieve goals and determine the division of tasks for the parties involved; 3) Implementation of religious Friday program activities is carried out by carrying out religious Friday activities in accordance with the plans and rules that have been made; 4) Supervision of religious Friday program activities using two steps namely; direct participation and motivation of teachers and students; 5) Evaluation of religious Friday activities is going well and in accordance with the principles in the evaluation such as: continuous, comprehensive, objective.